2020
DOI: 10.3389/fpsyg.2020.01411
|View full text |Cite
|
Sign up to set email alerts
|

Dichotic Perception of Lexical Tones in Cantonese-Speaking Congenital Amusics

Abstract: Congenital amusia is an inborn neurogenetic disorder of musical pitch processing, which also induces impairment in lexical tone perception. However, it has not been examined before how the brain specialization of lexical tone perception is affected in amusics. The current study adopted the dichotic listening paradigm to examine this issue, testing 18 Cantonese-speaking amusics and 18 matched controls on pitch/lexical tone identification and discrimination in three conditions: non-speech tone, low syllable vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“… 2 Following Xi et al (2010) , we compared amplitudes of F3 and F4 and added this as an extra within-subject factor Electrode to probe into the hemispheric pattern, which indicated that the main effect or interactions of Electrode with other factors were not significant ( p s > 0.1). Despite the low spatial resolution of ERP, the result as a preliminary sign manifested that the perception of Mandarin lexical tones is supported by neither one specific area nor a single hemisphere ( Gandour et al, 2004 ; Witteman et al, 2011 ; Price, 2012 ; Si et al, 2017 ; Liang and Du, 2018 ; Shao and Zhang, 2020 ). …”
mentioning
confidence: 75%
“… 2 Following Xi et al (2010) , we compared amplitudes of F3 and F4 and added this as an extra within-subject factor Electrode to probe into the hemispheric pattern, which indicated that the main effect or interactions of Electrode with other factors were not significant ( p s > 0.1). Despite the low spatial resolution of ERP, the result as a preliminary sign manifested that the perception of Mandarin lexical tones is supported by neither one specific area nor a single hemisphere ( Gandour et al, 2004 ; Witteman et al, 2011 ; Price, 2012 ; Si et al, 2017 ; Liang and Du, 2018 ; Shao and Zhang, 2020 ). …”
mentioning
confidence: 75%
“…Finally, all the identified brain regions were located in the right hemisphere. In right-handed healthy humans, the right hemisphere is more specialized in musical and non-verbal processing, such as pitch discrimination, timbre detection, and musical structure processing, while the left hemisphere is more dedicated to linguistic and verbal processing, such as the processing of spoken words, digits, and syllables ( 82 ). CA mainly manifests as pitch perception and pitch memory impairments ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that learning an alphabetic script boosts phonological awareness at the behavioral level (Morais et al, 1979;Cheung et al, 2001;Shu et al, 2008;. Phonological awareness usually refers to the ability to analyze the spoken language into smaller units such as phonemes (Liberman et al, 1974).…”
Section: The Effect Of Alphabetic Literacymentioning
confidence: 99%
“…Phonological awareness usually refers to the ability to analyze the spoken language into smaller units such as phonemes (Liberman et al, 1974). Since lexical tone is a suprasegmental unit that distinguishes word meanings in tonal languages, tone awareness can be considered as a component of phonological awareness, which involves the ability to recognize and extract the lexical tone from a speech unit (Shu et al, 2008;Li and Suk-Han Ho, 2011). For example, Cheung et al (2001) (Morais et al, 1979;Read et al, 1986;Morais, 2021).…”
Section: The Effect Of Alphabetic Literacymentioning
confidence: 99%
See 1 more Smart Citation